Handbook of medical imaging. Volume 1, - Beutel, Jacob; Kundel, Harold L.; Van Metter, Richard L. (SPIE, 2000)
This book examines x-ray imaging physics and reviews linear systems theory and its application to signal and noise propagation. The first half addresses the physics of important imaging modalities now in use: ultrasound, CT, MRI, and the recently emerging flat panel x-ray detectors and their application to mammography. The second half describes the relationship between image quality metrics and visual perception of the diagnostic information carried by medical images.
Keywords: Diagnostic imaging -- Handbooks, manuals, etc.; Imaging systems in medicine -- Handbooks, manuals, etc.; Diagnostic imaging.; Psychophysics.; elektronické knihy; electronic books